Framing Shale Gas for Policy-Making in Poland. Issue 1 (2nd January 2017) - Lis, Aleksandra; Stankiewicz, Piotr
Abstract: Despite enthusiasm about new gas reserves, shale gas has not come to Poland without controversies. This study examines how shale gas has been framed as a public issue by political and business elites, experts, local communities and civil society organizations. Through a frame analysis, we found three main frames about shale gas: shale gas as a novel economic resource, as a strategic resource for energy security and as a threat. However, only the first two frames, proposed by political and business elites, have shaped the policy process. The third frame, constructed by local actors and civil society groups, has had minimal impact. We explain this exclusion drawing on the deficit model of risk communication. This approach reveals that Polish experts, and business and political actors, during their interactions with local groups, have framed proponents of the threat frame as 'incompetent actors' effectively excluding the threat frame from policy processes.